PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN PEMBELAJARAN ONLINE DALAM MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR FISIKA PESERTA DIDIK KELAS X RPL 2 SMK NEGERI 1 NEGARA - I Ketut Sudiatmika (Widyadari : Jurnal Pendidikan, 2020)
The purpose of this study was to determine the independence and learning outcomes of students' physics through the application of the Problem Solving learning model with online learning in class X RPL 2 SMK Negeri 1 Negara in the 2019/2020 academic year. This type of research is classroom action research (PTK). The cycle of activities consisting of planning, action, observation, and reflection. The research subjects were students of class X RPL 2, totaling 36 people. The object of this research is independence and learning outcomes of physics. The data analysis used the observation method and the test method. The learning independence of students at the first meeting reached 9.18 at the second meeting increased to 11.54 and at the third meeting to 12.56. The learning outcomes of students in the first cycle an average of 67.31 students' learning outcomes increased in the second cycle to 82.05. Classical completeness of students increased from 38.39% to 88.89% in cycle II. The results showed that the application of the problem solving learning model with online learning could improve learning independence and physics learning outcomes for class X RPL 2 SMK Negeri 1 Negara in the 2019/2020 academic year.